THE USE OF THE BLINDFOLD GAMES TECHNIQUE TO IMPROVE THE VOCABULARY MASTERY OF STUDENTS AT SMPN 4 SUNGGUMINASA - A. Nurul Muntasya; Syarifuddin Dollah; Sultan Baa (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
The purpose of this research was to find out the use of “the Blindfold game technique” in improving the vocabulary mastery of students at SMPN 4 Sungguminasa. The method used in this research was pre-experiment with one group pretest-posttest. The population in this study were students of Class VIII at SMPN 4 Sungguminasa in the 2022/2023 academic year. This research used a cluster random sampling technique. The sample of this research was Class VIII C, which consisted of 30 students. The results of this study that there were a significant increase in students vocabulary mastery after the students were given treatment. This can be seen by the mean score between the pre-test (52.53) and the post-test (79.33). It means that the use of the Blindfold as games was able to improve students vocabulary mastery. This game helps the students to enhance their learning on vocabulary mastery.